An OVERVIEW OF KNOWLEDGE AND NEEDS REGARDING THE USE OF DIGITAL DEVICES AND SELF-MANAGEMENT AMONG HEART FAILURE PATIENTS AT ARIFIN ACHMAD : GAMBARAN PENGETAHUAN DAN KEBUTUHAN TERHADAP PENGGUNAAN PERANGKAT DIGITAL DAN SELF-MANAGEMENT PADA PASIEN GAGAL JANTUNG DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Widya Restika; Rizka Febtrina; Dini Maulinda; M. Zul’irfan (Journal of Health and Cardiovascular Nursing, 2026)
Heart failure is a chronic disease requiring long-term management through improved disease understanding, self-management abilities, and digital technology support. While digital device utilization in heart failure care continues to expand, patients’ knowledge, perceived needs, and self-management abilities remain varied. This study aimed to describe the levels of knowledge, needs related to digital device use, and self-management among patients with heart failure. A descriptive quantitative design was applied with a sample of 48 heart failure patients selected through purposive sampling. Research instruments included a knowledge questionnaire adapted from the Digital Health Literacy Instrument (DHLI), a digital device needs questionnaire based on the SKF-DK-HF, and a self-management questionnaire adapted from the Self-Care of Heart Failure Index (SCHFI) version 7.2. Data were analyzed using univariate analysis with frequency distributions and percentages. The results showed that most respondents were aged 46–55 years (33.3%) and female (66.7%). The majority demonstrated good knowledge regarding digital device use (64.6%), moderate levels of digital device needs (58.3%), and more than half had adequate self-management ability (58.3%).These findings indicate that although most patients possess good knowledge and adequate self-management, optimizing digital device use and strengthening consistent self-care practices remain necessary.